2020
DOI: 10.1111/jen.12795
|View full text |Cite
|
Sign up to set email alerts
|

Fluctuating environments impact thermal tolerance in an invasive insect species Bactrocera dorsalis (Diptera: Tephritidae)

Abstract: There is increasing evidence of changes in the global climate system due to anthropogenic activities (IPCC, 2014). An emerging concern is that the incidence and severity of climate "presses" and "pulses" such as extreme variation in temperatures and rainfall, heatwaves, cold snaps, drought and floods are increasing globally

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 66 publications
(122 reference statements)
0
15
0
1
Order By: Relevance
“…Lastly, our methodology opens up further opportunities to model population dynamics based upon the responses to micro-climatic environments (as [ 49 ] have done for in a tephritid fly Bactrocera dorsalis ). The effects of temperature and exposure on other demographic parameters like development time and fecundity in order to estimate the thermal effects on the population growth rate are reasonably understood.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Lastly, our methodology opens up further opportunities to model population dynamics based upon the responses to micro-climatic environments (as [ 49 ] have done for in a tephritid fly Bactrocera dorsalis ). The effects of temperature and exposure on other demographic parameters like development time and fecundity in order to estimate the thermal effects on the population growth rate are reasonably understood.…”
Section: Discussionmentioning
confidence: 99%
“…The effects of temperature and exposure on other demographic parameters like development time and fecundity in order to estimate the thermal effects on the population growth rate are reasonably understood. Under laboratory conditions daily temperature fluctuations (DTF) did not affect development time and fertility for Rhodnius prolixus [ 49 ]. However, fecundity was lower in females reared at DTF than at constant temperature, and males had higher body mass reduction rate and lower survival in the DTF regime, suggesting higher costs associated to fluctuating thermal environments [ 50 ].…”
Section: Discussionmentioning
confidence: 99%
“…The trade of agricultural products requires licenses certifying their nonnegative effect on the society and environment of the destination country (Rosselkhoznadzor). Sanitary and phytosanitary measures defined by the Russian plant protection organization as requirements for the import of citrus fruits set the minimum quality standards which the export countries need to respect to reach the Russian citrus market (Mutamiswa et al 2020 ).…”
Section: Research Backgroundmentioning
confidence: 99%
“…Epigenetic signature of invasiveness in B. dorsalis B. dorsalis has a strong invasion ability, with underlying physiological, morphological and behavioral mechanisms facilitating its expansion to new environments (Gu et al, 2019;Mutamiswa et al, 2020;Pieterse et al, 2017), consisting of a key component of the invasiveness in this species (Froerer et al, 2010;Liang et al, 2001). In this study, in consistent with stronger flight capability in B. dorsalis (Chen et al, 2015;Lane et al, 2014), we found more genes involved in flight capacity were modified by histone modifications inB.…”
Section: Conserved Patterns Of H3k4me3 and H3k27me3 Between B Dorsali...mentioning
confidence: 99%